Strategi Sekolah Dalam Menanamkan Dimensi Beriman Bertakwa Kepada Tuhan Yang Maha Esa dan Berakhlak Mulia Di Sds Islam Terpadu : Profil Pelajar Pancasila Dimensi Beriman Bertaqwa kepada Tuhan Yang Maha Esa dan Berakhlak Mulia - Susilawati, Wiwik Okta; Anggrayni, M.; Prastika, Nadia (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
SDS IT Al-Bina 01 Koto Baru is an educational institution that stands out in the formation of student character, especially in one dimension of the Pancasila Student Profile (P3), namely faith, devotion to God Almighty, and noble morals. This study aims to explore the strategies implemented by schools in instilling these values ​​through various aspects, such as religious aspects, personality, social relations, relations with nature, and love for the nation. The approach used in this study is qualitative with data collection methods through observation, interviews, and documentation. Data analysis was carried out through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, source and technique triangulation techniques were used. The results of the study revealed that the school implemented a strategy based on the moral knowing, moral feeling, and moral action approaches. This strategy is implemented through various programs such as the determination of Graduate Competency Standards (SKL), school discipline rules, superior programs, routine activities, and the use of liaison books between teachers and parents. All of this is designed to instill the values ​​of faith and noble morals in students in the Integrated Islamic Elementary School environment. This approach has proven effective in fostering religious values ​​and noble character in students. Keywords: School Strategy, Profile of Pancasila Students, Dimensions of Faith, Faith in Almighty God and Noble Morals, Integrated Islamic SDS